Students’ Perception on The Use Of ChatGPT in Research Writing - Yeki, Dominikus; Bunau, Eusabinus; Rezeki, Yanti Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
The integration of Artificial Intelligence in education has transformed how students engage with academic tasks, particularly in research writing. Among various AI applications, ChatGPT has emerged as a widely used language model that assists students in generating, organizing, and refining research writing process. This study investigates students’ perceptions and behavioral intentions toward using ChatGPT in academic research writing, employing the Technology Acceptance Model as the analytical framework. A quantitative survey design was implemented involving 205 undergraduate students from the English Education Study Program at Tanjungpura University, representing the batch of 2020 to 2022. Data were collected through a 20 item online questionnaire using a five-point Likert scale and analyzed using descriptive statistics including means and standard deviations. The findings show consistently high perceptions across all constructs of the model, with Perceived Usefulness (M = 3.80, SD = 1.05), Perceived Ease of Use (M = 3.78, SD = 1.00), Attitude Toward Usage (M = 3.79, SD = 1.02), and Behavioral Intention (M = 3.96, SD = 0.97), all categorized as high. These results indicate that students find ChatGPT beneficial, easy to use, and supportive in enhancing writing quality and productivity. The results also suggest a strong intention to continue using AI tools for academic writing, reinforcing the relevance of the Technology Acceptance Model in the higher education context. This study concludes by emphasizing the importance of promoting ethical AI literacy and critical engagement to ensure that ChatGPT complements, rather than replaces, students’ intellectual and creative efforts.